Direction and Reverberation Preserving Noise Reduction of Ambisonics Signals - Herzog, Adrian; Habets, Emanuël (IEEE/ACM Transactions on Audio, Speech and Language Processing, 2020)
Ambisonics encodes the directional information of a sound field w.r.t. a reference position in an efficient and scalable way. However, the sound field might contain undesired noise. Reducing the noise while preserving the directional distribution of all sound field components is a challenging task. Recently, the present authors proposed a direction-preserving noise reduction method for higher-order Ambisonics (HOA) signals, which, in contrast to e.g. binaural beamforming methods, yields a HOA signal at the output. In this work, we investigate the direction-preserving noise reduction method further and compare it against a beamforming-based method and the matrix multi-channel Wiener filter. Different methods to estimate the power spectral densities which are needed for the noise reduction methods are discussed. Moreover, a method to preserve the reverberation of the desired signal is proposed. In the evaluation, the discussed methods are compared for different speech sources in anechoic and reverberant conditions and different noise types.
CRIS-Team WoS Importer:2020-09-11